Analysis of Complex Nonlinear Dynamic Systems by Means of Partial Models. Convergence of Iterative Procedures - Stańczyk, T.L. (Engineering Transactions, 1993)
Problems of iterative convergence in the analysis of complex dynamic systems with the use of partial models are dealt with. Nonlinear systems are considered. An example of some nonlinear system and the suitable iteration process are presented. The time analysis is also dealt with. On the assumption that the solutions of the system can by expanded in power series with respect to a small parameter, the general condition of convergence is formulated. Limitations for the successive derivatives of nonlinear stiffness characteristics are determined as a consequence of the convergence conditions of the procedures.